CHARACTERISTICS OF LYMPHADENITIS IN HOSPITALISED PATIENTS BANDAR LAMPUNG-INDONESIA - Hetti Rusmini; Retno Ariza; Nur Rahayu Permana Sari (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Lymphadenitis is an inflammation of the lymph nodes caused by a variety of microorganisms such as Mycobacterium tuberculosis, human immunodeficiency virus (HIV), and other microorganisms. Patient characteristics lymphadenitis diverse views on the etiology, age, gender, and lymph nodes affected.Purpose: The purpose of this study was to describe the characteristics of patients with lymphadenitis.Methods: The design of this study is descriptive cross sectional method is done by looking at medical records of patients in Dr. H. Abdul Moeloek hospital Bandar Lampung 2015. The samples were taken using stratified random sampling technique so that 161 samples used in this study.Results: The results showed the frequency distribution of patients with tuberculous lymphadenitis is the highest (57.14%), lymphadenitis other microorganisms (21.74%), and HIV lymphadenitis (21.12%). The frequency distribution of TB lymphadenitis patient age was 15-24 years (45.7%), patients with HIV lymphadenitis most at the age of 45-64 (29.4%), while the age of the patient lymphadenitis other microorganisms highest in the 15-24 age (28 , 6%). The frequency distribution of TB lymphadenitis gender, HIV and most were female (58.7% and 52.9%), while the frequency distribution of the sexes in most other microorganisms lymphadenitis patients were male (54.3%).Conclusion: The frequency distribution locations lymphadenitis TB, HIV and other microorganisms most was the neck (regio colli) (96%, 55.9% and 57.1%).